Weaponizing Radioactive Medical Waste - The Looming Threat - Shreekumar Menon; Vagish Kumar L.S. (International Journal of Nuclear Security, 2019)
Across the globe, use of radioactive substances for medical treatment, by hospitals has resulted in generation of toxic wastes on a large scale. Disposal of these wastes are being entrusted to waste disposal vendors. Environmental concerns, pressures, restrictions and high labor costs, compel these vendors to dump these wastes in third world countries, where enforcement and awareness are substantially low. Unrestricted access to these waste dumps is an open invitation to terror organizations to extract toxic substances and fabricate crude dirty bombs to threaten public safety, and cause low-level contamination of sensitive installations. It is therefore imperative to create an international organization to monitor, regulate, and supervise the safe disposal of toxic radioactive wastes.
Keywords: Radioactive medical waste; radioisotopes; nuclear medicine; radiological terror; radiological dispersal devices; dirty bomb